HUBUNGAN BAURAN PEMASARAN DAN KUALITAS LAYANAN DENGAN KEPUTUSAN PEMBELIAN BUAH LOKAL DI UD. SARI BUAH SEGAR KOTA SALATIGA - Ayu Puspita Sari; Nuswantara Bayu (Jurnal Pertanian Agros, 2026)
Competition between local and imported fruits, which continue to dominate the market, poses a challenge in increasing purchasing decisions for local fruits. This study aims to determine the relationship between marketing mix and service quality and purchasing decisions of local fruits at UD. Sari Buah Segar, Salatiga City. The research employed a quantitative descriptive method with a sample of 40 respondents. The variables analyzed included price (X₁), product (X₂), promotion (X₃), reliability (X₄), responsiveness (X₅), and assurance (X₆) as independent variables, and purchasing decision (Y) as the dependent variable. Data were analyzed using validity and reliability tests, descriptive analysis, and Spearman Rank correlation with a significance level of α = 0.05. The results show that price, product, reliability, responsiveness, and assurance have positive and significant relationships with purchasing decisions. Meanwhile, promotion has a positive but not significant relationship. The findings suggest that local fruit businesses should prioritize maintaining consistent product quality, ensuring price affordability, and improving service quality as key factors in influencing consumers purchasing decisions.